Formulation and Evaluation of Weaning Foods Prepared from Multigrain Flour and Powdered Milk - Saheefa Shaheen; Nazia Tabassum; Rashid Imran Ahmad Khan; Sadaf Ahmad (Archives of Current Research International, 2024)
Aims: Children after 6 months need to shift from breast milk to weaning food. The present study aims to develop low cost nutritious weaning foods to fulfil the increased nutritional requirements during this phase of growth. Study Design: The present study involved development of three different samples of low cost weaning foods prepared with multigrain flour (combination of rice flour, wheat flour and gram flour in the ratio of 2:1:0.5) mixed with milk powder (5%, 7.5% and 10% of the total flour mixture). Sensory, physicochemical and cost analyses were performed for the samples. Place and Duration of Study: University Polytechnic (Boys), Aligarh Muslim University, Aligarh, Uttar Pradesh, between January 2016 and July 2016. Methodology: Sensory evaluation was done on a 9 point hedonic scale after preparing the samples for consumption by adding either water or milk. Physicochemical properties of the developed samples such as moisture content, ash content and protein content were assessed during storage at room temperature (25-32˚C) for 2 months in airtight laminated aluminium film packing material. Results: In sensory of samples prepared with water, sample 3 was found to be the most preferred sample while in case of samples prepared with milk, sample 1 was found to be the best in sensory quality. All the developed weaning food samples were found to be stable during 50 days of storage. Moisture content, Protein content and Ash content of the samples ranged from 4.84 to 10.38%, 13.23 and 16.29% and 1.22 to 1.54% respectively. Samples with more milk powder showed higher protein content and fat content. Conclusion: The prepared weaning food samples had comparable physicochemical and sensory characteristics and lower cost than the commercially available weaning foods. They will be helpful in fulfilling the nutritional requirement of the vulnerable sections of society including middle-income groups (MIG) and low-income groups (LIG) consumers and overcoming malnutrition.